PD‐1/PD‐L1 negative schwannoma mimicking obstructive bronchial malignancy: A case report. Issue 8 (8th June 2020) - Zhou, Daibing; Xing, Xiaoyan; Fan, Jie; Zhang, Youzhi; Liu, Jie; Gong, Yi
Abstract: Schwannomas are homogeneous tumors of schwann cells and occur at peripheral and cranial nerves on the upper limbs, the head and neck area. Rarely, a bronchial schwannoma may appear in the lung and be misdiagnosed as lung neoplasms. Here, we report a 56‐year old woman with a 5.8 × 7.0 × 2.8 cm lesion in her right upper lobe bronchus. The lesion had a maximum standardized uptake value (SUVmax ) of 8.5 by 18‐fluorodeoxyglucose positron emission tomography (FDG‐PET). Bronchoscopy showed a mass obstructing the bronchus that bled easily. Despite repeated biopsies, a lung malignancy could not be excluded, and surgical resection was subsequently performed. Pathological examination demonstrated a primary bronchial schwannoma that was positive for molecular markers S‐100 and SOX‐10, negative for immune checkpoint marker PD‐1/PD‐L1 but also demonstrated certain uncommon pathological features. This case highlights the heterogeneity of bronchial masses and the diagnostic challenge for differentiating benign and malignant tumors in the thorax. Key points: Rare bronchial schwannoma mimics lung malignancy and poses a diagnostic challenge. This case of bronchial schwannoma, unlike peripheral schwannoma, lacks PD‐L1. Pathological features indicate autonomic nerve origin for pulmonary schwannomas.